Focal delivery of AAV2/1-transgenes into the rat brain by localized ultrasound-induced BBB opening - Alonso, Angelika; Reinz, Eileen; Leuchs, Barbara; Kleinschmidt, Jürgen; Fatar, Marc; Geers, Bart; Lentacker, Ine; Hennerici, Michael G.; de Smedt, Stefaan C.; Meairs, Stephen (Molecular therapy. Nucleic Acids, 2013)
Delivery of drugs and macromolecules to the central nervous system (CNS) is hindered by the blood-brain barrier (BBB). Several approaches have been used to overcome this hindrance to facilitate the treatment of various CNS diseases. We now present results showing that chimeric adeno-associated virus 2/1 (AAV2/1) particles containing the coding region for the LacZ gene are efficiently delivered into the rat brain upon intravenous (IV) administration after BBB opening by focused ultrasound in the presence of vascular acoustic resonators. We show that the transgene is correctly and efficiently expressed in cells located in the neighborhood of the insonated focus, especially in the vicinity of small vessels and capillaries. Histochemical LacZ staining allows the identification of large amounts of cells expressing the enzymatically active protein. Using double immunofluorescence (IF) with antibodies against tubulinIII and bacterial LacZ, we identified these cells to be mostly neurons. A small proportion of the transduced cells was recognized as glial cells, reacting positive in the IF with antibodies against astrocytic markers. These results demonstrate that our approach allows a very specific, localized, and efficient expression of intravenously administered transgenes in the brain of rats upon ultrasound-induced BBB opening.